Designing 3D Polymeric Structures through Capillary Wetting on Colloidal Monolayer. (30th October 2022) - Lee, Hyeong Jun; Park, Sanghyuk; Kim, Jong Bin; Kim, Shin‐Hyun
Abstract: Colloidal lithography has provided a facile means to create regular micro‐ and nano‐patterns by employing colloidal crystals as masks. However, the patterns are usually restricted to 2D as most techniques do not exploit the spherical shape of colloidal masks. Here, 3D structures are designed by utilizing capillary wetting of liquified photoresists on colloidal monolayers of silica particles. The silica particles are anchored at planar air‐photoresist interfaces to have an equilibrium contact angle without interfacial deformation for thick polymer layers. By contrast, when the polymer layers are thin enough, they wet the colloidal monolayer by forming periodic wavy interfaces to provide a constant Laplace pressure. The photo‐crosslinking of the photoresist and subsequent removal of silica particles leave behind periodic nanostructures with 3D‐undulated surfaces. Importantly, the structure and waviness are further controllable by adjusting the polymer thickness relative to the particle radius. As the shape of the interface is determined by capillarity, the 3D structures are reproducible as long as the dimension is smaller than the capillary length. The use of photoresists enables the production of micropatterns of the periodic wavy structures by photolithography. As one of the potential applications, structurally‐colored patterns are demonstrated with enhanced plasmonic and diffraction colors. Abstract : 3D undulated surfaces are directly created by capillary wetting of molten polymer on particle monolayers. The surface shape is determined by constant Laplace pressure to have constant mean curvature, where waviness is controllable with the relative volume of the polymer to particles. The wavy structures are micro‐patternable by photolithography and their dimensions can be increased up to the capillary length.